DEVELOPMENT OF CYCLONE COAL BURNER FOR FUEL OIL BURNER SUBSTITUTION IN INDUSTRIES - Sumaryono SUMARYONO (Indonesian Mining Journal, 2009)
The high fuel oil price forces the industries to seek cheaper alternative energy. Coal is the most promising alternative energy in Indonesia. To face this situation, R & D Centre for Mineral and Coal Technology (tekMIRA) has developed a cyclone burner. This burner has the combustion characteris- tics nearly the same as the fuel oil burner that this burner may alter the fuel oil burner in various industrial facilities, such as steam boiler, oil heater, rotary dryer, metal smelter and heat exchanger. The cyclone burner combusting coal powder of -30 mesh may match the energy output of the former altered fuel oil burner. The burning of coal emits long flame and the combustion rate may be con- trolled by a variable feeder. It may be shut of and then put on instantaneously as it is practiced in oil burner. Fine adjustment of the coal and air supply were performed and this burner was set up in vertical and horizontal position. In this substitution 1 litre fuel oil was substituted by 1.5 up to 1.8 kg of coal of 5700 kcal/kg.